2005
DOI: 10.1007/s00439-005-1302-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreased transcription of the human FCGR2B gene mediated by the -343 G/C promoter polymorphism and association with systemic lupus erythematosus

Abstract: The role for inhibitory Fc gamma receptors class IIb (FcgammaRIIb) in the onset, progression and severity of several animal models of autoimmune diseases is well established. By contrast, the pathogenic potential of FcgammaRIIb in human autoimmune diseases remains largely unknown. Here we report the identification of a polymorphism in the human FCGR2B promoter (dbSNP no. rs3219018) that is associated in homozygosity with systemic lupus erythematosus (SLE) phenotype in European-Americans (OR=11.1, P=0.003). Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 33 publications
4
123
1
Order By: Relevance
“…Genetic variants of CD32B gene are reported to affect the expression and function of this receptor and be associated with select autoimmune conditions in both mice and humans (40)(41)(42). We cannot completely exclude the possibility that specific CD32B polymorphisms, known to affect CD32B expression, partially account for our observations in RA; however, the extremely low prevalence of these polymorphisms limits their potential influence on our findings (41,42).…”
Section: Discussionmentioning
confidence: 76%
“…Genetic variants of CD32B gene are reported to affect the expression and function of this receptor and be associated with select autoimmune conditions in both mice and humans (40)(41)(42). We cannot completely exclude the possibility that specific CD32B polymorphisms, known to affect CD32B expression, partially account for our observations in RA; however, the extremely low prevalence of these polymorphisms limits their potential influence on our findings (41,42).…”
Section: Discussionmentioning
confidence: 76%
“…rs 3219018. A nested PCR amplified a 15-kb region specific for FCGR2B, which was followed by amplification of the promoter region, with primers as previously described (22). The PCR products were purified using Exosap and sequenced using an ABI 3730 sequencer.…”
Section: Methodsmentioning
confidence: 99%
“…A polymorphism in the promoter region of FCGR2B, rs3219018, has been associated with changes in FcγRIIb expression and SLE in Caucasians (22), and it might have an additional effect on susceptibility to infection. We genotyped 96 Kenyan controls and found no minor alleles, despite finding a MAF of 0.16 in 90 U.K. Caucasians.…”
mentioning
confidence: 99%
“…Polymorphisms in the human FCGR2B gene are associated with the SLE phenotype (21)(22)(23)(24)(25)(26). We have recently demonstrated that polymorphisms in the regulatory region of FCGR2B form two major haplotypes and that the less frequent 2B.4 haplotype is significantly overrepresented in SLE patients (22).…”
Section: T He Only Inhibitory Igg Fcr In the Classical Fcr Family (1mentioning
confidence: 99%